The transition of breastfeeding children with cleft palate and lip among women - Rosangela da Silva Santos; Janaina Pinto Janini; Helaine Maria da Silva Oliveira (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To discuss the maternal transition in the breastfeeding process of children with cleft lip and palate, from the perspective of the transition theory. Method: Qualitative research of the case study type. The semi-structured interview was used as a data collection instrument. The results were analyzed from the Transition Theory. Results: The participant presented the transitions: situational, developmental and health-illness due to the change of social roles, the need to care for the child with malformation and the changes in her life due to her child's illness. It was identified, in the participant, the difficulty of exercising maternal breastfeeding care, interfering in its developmental and situational transition. Conclusion and implications for practice: The transitions were ineffective in taking into account the transitions covered. The presence of a nursing professional in the evaluation, follow-up and supplementation of the mother in the suckling of children with cleft lip and palate is essential to achieve the healthy transition.